Analysis of the design parameters related to a fixed-pitch straight-bladed vertical axis wind turbine - Islam, Mazharul; Fartaj, Amir; Carriveau, Rupp (Sage Publications, 2008)
The fixed-pitch straight-bladed vertical axis wind turbine (SB-VAWT) is one of the simplest types of wind turbine. One of the main challenges of wide spread application of the smaller-capacity SB-VAWT is to design and develop it in a cost-effective manner. The overall cost of the SB-VAWT will mainly depend on judicious choice of multiple design parameters. An attempt has been made in this paper to identify and critically analyze the main design parameters related to smaller-capacity fixed-pitch SB-VAWT. It has been demonstrated in this paper that proper selections of these parameters are vital for a cost-effective smaller-capacity SB-VAWT which can be considered as a candidate for urban and off-grid rural applications.